Thermal cyclic fatigue damage evolution of fiber-reinforced ceramic-matrix composites under constant loading. Issue 9 (2nd September 2022) - Li, Longbiao; Reynaud, Pascal; Fantozzi, Gilbert
ABSTRACT: Under thermal cyclic fatigue loading, temperature and cyclic-dependent damage mechanisms affect thermal fatigue damage evolution in fiber-reinforced ceramic-matrix composites (CMCs). Stress-strain hysteresis loops occur with the changing of temperature and correspond to internal damage evolution in CMCs. In this work, fatigue hysteresis-based damage features, including hysteresis-based dissipated energy, hysteresis modulus, hysteresis width, and peak strain, were developed to monitor thermal cyclic fatigue damage evolution in CMCs considering synergistic impacts of thermal and mechanical loading. Experimental thermal fatigue damage evolution of the 2.5D woven C/SiC composite subjected to various thermal fatigue loads were predicted with the newly developed fatigue hysteresis-related damage parameters. The effects of the composite's material features, peak stress, damage state, and cycle number on thermal fatigue damage evolution in the C/SiC composite were analyzed. Abstract : uf0001